La géopolitique des droits humains - Seurin, Jean-Louis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
The universality of the ideology of Human Rights is presently enjoying increased interest inspite of the limited results and disappointing concrete realizations achieved in this area. At the time of the adoption of the Universal Declaration of Human Rights, the universality of the doctrine of Human Rights was only an illusion and the problems raised by the application of subsequent international accords have made evident the political conflicts which are at play behind the human rights debate. Presently, one may accurately speak of a "geopolitic of human rights". Starting from the precept that the best way to resolve opposing points of view is to begin with reality, the author examines the relative situation of Human Rights in three groups which are each relatively homogeneous : the Atlantic zone regrouping the pluralist constitutional democracies; the totalitarian countries including the Soviet Union, the Eastern Bloc countries and the communist countries of Asia and, finally, the zone of non-aligned countries of the "third world".